2020
DOI: 10.3758/s13428-019-01338-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous tracking of psychophysical detection thresholds and evoked potentials to study nociceptive processing

Abstract: Measuring altered nociceptive processing involved in chronic pain is difficult due to a lack of objective methods. Potential methods to characterize human nociceptive processing involve measuring neurophysiological activity and psychophysical responses to well-defined stimuli. To reliably measure neurophysiological activity in response to nociceptive stimulation using EEG, synchronized activation of nerve fibers and a large number of stimuli are required. On the other hand, to reliably measure psychophysical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…3. In earlier studies, this effect was also found significant, but had a larger effect size (Doll et al 2016a, b;van den Berg et al 2020). Altered habituation appears to play an important role in several types of chronic pain syndromes, and is therefore an important phenomenon to observe when assessing nociceptive processing (Agostinho et al 2009;Rodriguez-Raecke et al 2014;Valeriani et al 2003).…”
Section: Effect Of Intra-epidermal Stimulus Properties On Detection Pmentioning
confidence: 81%
See 3 more Smart Citations
“…3. In earlier studies, this effect was also found significant, but had a larger effect size (Doll et al 2016a, b;van den Berg et al 2020). Altered habituation appears to play an important role in several types of chronic pain syndromes, and is therefore an important phenomenon to observe when assessing nociceptive processing (Agostinho et al 2009;Rodriguez-Raecke et al 2014;Valeriani et al 2003).…”
Section: Effect Of Intra-epidermal Stimulus Properties On Detection Pmentioning
confidence: 81%
“…Measuring this habituating behavior can be used to assess altered nociceptive processing. A decreased habituation of P2 amplitude over time or over the amount of repeated stimuli has been related to chronic pain in earlier literature in patients with migraine (Valeriani et al 2003), chronic low back pain (Vossen et al 2015) and fibromyalgia (de Tommaso et al 2011).…”
Section: Effect Of Intra-epidermal Stimulus Properties On Evoked Potementioning
confidence: 92%
See 2 more Smart Citations
“…Previous electrophysiological studies exploring use-dependent plasticity are typically based on a total sample size between 15-44 participants (Kühnis et al, 2014; Pantev et al, 2001; Vuust et al, 2008). Moreover, studies using the same intra-epidermal electrical stimulation to elicit nociceptive electrophysiological responses as in the current study report total sample sizes of 5-20 participants (Biurrun Manresa et al, 2018; Mouraux et al, 2014, 2010; van den Berg et al, 2020). To ensure a robust estimate of our neurophysiological effect, a total sample of 40 participants was recruited for the current study.…”
Section: Methodsmentioning
confidence: 98%